THE MEANING OF CARING FOR PAPUA IN THE PERSPECTIVE OF THE 2ND PRECEPT OF PANCASILA IN DRIYARKARA’S VIEW - Meidinata, Marianus Ivo; Ryan Puan Renna, Hendrik (PRODI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN STKIP PGRI SUMENEP, 2022)
ABSTRACT In this study, the author focuses on the meaning of caring for the people and the land of Papua. This research takes a phenomenological philosophical method with a qualitative approach; and a literature study as a data collection method. The meaning of this concern is seen from the perspective of the second principle of Pancasila according to Driyarkara. The author tries to see the reality of the government's concern for Papua to overcome the humanitarian crisis that exists there. This study finally concluded that order, peace, good material conditions, general welfare and other things that the state organizes for the Papuan people are aimed at humanity – for human development and perfection. This concern for Papua implies that Papuans are also humanitarian activists even though they have suffered injuries. This government's concern is a sign of the country's progress with the creation of Pancasila people who uphold humanity. Several motives encourage this attitude renewal, including love and compassion by viewing Papua as a family. In this case, the conscience of the Indonesian people has returned, especially to the sensitivity of humanity. ABSTRAK Pada studi ini, penulis mengambil fokus pada makna kepedulian kepada masyarakat dan tanah Papua. Penelitian ini mengambil metode filosofis fenomenologis dengan pendekatan kualitatif; dan studi kepustakaan sebagai metode pengumpulan data. Makna kepedulian ini dilihat berdasarkan perspektif Pancasila sila kedua menurut Driyarkara. Penulis mencoba melihat realitas kepedulian pemerintah kepada Papua untuk mengatasi krisis kemanusiaan yang ada di sana. Studi ini akhirnya sampai pada suatu kesimpulan bahwa ketertiban, kedamaian, keadaan material yang baik, kesejahteraan umum dan hal lain yang diselenggarakan negara untuk masyarakat Papua ditujukan untuk perikemanusiaan – untuk perkembangan dan penyempurnaan manusia. Kepedulian kepada Papua ini mengandung makna bahwa Papua juga merupakan penggiat kemanusiaan meskipun mereka telah mengalami luka. Kepedulian pemerintah ini menjadi tanda kemajuan negara dengan terciptanya manusia-manusia Pancasila yang menjunjung kemanusiaan. Ada beberapa motif yang mendorong pembaruan sikap ini antara lain cinta dan belas kasih dengan memandang Papua sebagai keluarga. Dalam hal ini, hati nurani bangsa Indonesia telah kembali khususnya akan kepekaan kemanusiaan.